Analysis of Nuclear Disruption and Binding of Intermediates in Host DNA Breakdown to Membranes After Infection of Escherichia coli with Bacteriophages T4 and T7 - Parson, Kathleen A. (1973)
Escherichia coli DNA polymerase I is implicated in the binding of intermediates in host DNA breakdown to membrane in T4-infected, but not T7-infected, cells. Nuclear disruption is observed in T4-infected polA1 mutant cells.